Tomosyn expression pattern in the mouse hippocampus suggests both presynaptic and postsynaptic functions - Boaz eBarak; Antionette eWilliams; Noa eBielopolski; Irit eGottfried; Eitan eOkun; Meghan A Brown; Ulf eMatti; Jens eRettig; Edward L Stuenkel; Uri eAshery (Frontiers Media S.A., 2010)
The protein tomosyn decreases synaptic transmission and release probability of vesicles, and is essential for modulating synaptic transmission in neurons. In this study, we provide a detailed description of the expression and localization patterns of tomosyn1 and tomosyn2 in the subareas of the mouse hippocampus. Using confocal and two-photon high-resolution microscopy, we show tomosyn1's differential distribution in the mouse hippocampus, concentrated mainly in the hilus and mossy fibers. Tomosyn colocalizes with several pre- and postsynaptic markers and is found mainly in glutamatergic synapses. Surprisingly, we found that tomosyn2 is expressed in the subiculum, CA1 and CA2 pyramidal cell bodies, dendrites and spines, and colocalizes with PSD95, suggesting a postsynaptic role. These results suggest that in addition to the well-characterized presynaptic function of tomosyn in neurotransmitter release, tomosyn2 might have a postsynaptic function, and place tomosyn as a more general regulator of synaptic transmission and plasticity.